2017
DOI: 10.1089/pho.2016.4252
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Transcutaneous and Intraoral Low-Level Laser Therapy After Extraction of Lower Third Molars: A Randomized Single Blind, Placebo Controlled Dual-Center Study

Abstract: The results of this study suggest that single-session intraoral LLLT is more effective than extraoral application for reducing postoperative pain. It was postulated that the differences between skin and mucosa could have effect on the results. Although intraoral use would allow closer application to the surgical site, the size of some laser devices precludes their use intraorally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 21 publications
3
36
0
16
Order By: Relevance
“…Other studies exhibited that LLLT produced a positive effect on reducing the degree of pain in patients who underwent surgical interventions. [10][11][12][13][14][15][16][17][18] Bjordal et al 39 in a systematic review demonstrated that adequate doses of photoradiation can significantly alleviate acute inflammatory pain by suppressing the levels of biochemical markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies exhibited that LLLT produced a positive effect on reducing the degree of pain in patients who underwent surgical interventions. [10][11][12][13][14][15][16][17][18] Bjordal et al 39 in a systematic review demonstrated that adequate doses of photoradiation can significantly alleviate acute inflammatory pain by suppressing the levels of biochemical markers.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated the beneficial effects of laser therapy on reducing pain, swelling and trismus after the surgical removal of impacted lower third molars. [10][11][12][13][14][15][16][17][18] Others revealed that the application of LLLT enhanced bone healing and mineralization in the sockets of rats exposed to diode laser radiation. [19][20][21][22][23] However, some studies found no additional benefits of using low-level lasers over the placebo in several conditions such as releasing pain after the extraction of primary 24 and permanent 25 teeth, reducing pain and swelling following third molar surgery, [26][27][28] improving pulp tissue healing after direct pulp capping in dogs, 29 and attenuating chronic orofacial pain in patients with temporomandibular dysfunction (TMD).…”
Section: Introductionmentioning
confidence: 99%
“…In all these studies, the third molar was the extracted tooth except in one study conducted on premolar's extraction sockets. 23 PBM effectively reduced post extraction pain as shown in 16 studies 5,6,13,[15][16][17][18][19][24][25][26][27][28][29][30][31] compared with placebo. In these studies, wavelengths ranged from 650 to 980 nm.…”
Section: Study Selectionmentioning
confidence: 77%
“…As previously mentioned, third molar extractions are among the most frequent oral surgery procedures, which is also commonly associated with postoperative pain, resulting in impaired quality of life during the postoperative course. In the literature, there is still a lack of evidence regarding PBMT effectiveness in reducing third molar extraction postoperative pain, where previous studies presented positive and others no difference compared to a control group ( 20 - 22 ). Also, there are no standardized protocols of PBMT considering the number of sessions, administration mode, and wavelengths ( 23 ).…”
Section: Discussionmentioning
confidence: 99%